Identifying Faculty Unionization Barriers at Kabul University - Alireza Rajabipoor Meybodi; Gholam Reza Bordbar; Joma Khan Kazimi; Ahsanullah Sazawar (Journal of Entrepreneurship and Business, 2022)
Pupose: This paper aims to unveil the faculty unionization barriers in Kabul University. To utilize its sources and opportunities effectively and efficiently, universities need a cooperated faculty members. One way that makes faculties maintain their rights and privileges legally and build an equitable system is to establish Faculty Union. The research question addressed is: why Kabul University as one of the most influential and mother University in Afghanistan, still could not formed Faculty union? Method: For data analysis, the authors use thematic analysis to investigate the research question. Result: The results of this study show that Faculty Unionization Barriers at Kabul University classify under five categories including; Political barriers, Cultural barriers, Strategic barriers, Structural barriers and Legal barriers. The researchers of this paper believes that all these five factors rovolves around one axle; lack of an strong organizational culture in Kabul University. The identified barriers could be a facilitator for Kabul university faculty members and helpful in collaboration and Intra-Organizational Integration.